Прикочуючий коток сівалки - Артеменко, Д. Ю.; Мажара, В. А.; Кислун, О. А.; Artemenko, D.; Mazhara, V.; Kyslun, O.; Артеменко, Д. Ю.; Мажара, В. А.; Кислун, О. А. (Український інститут інтелектуальної власності, 2015)
Корисна модель належить до галузі сільськогосподарського виробництва, зокрема до робочих органів просапних сівалок, і може бути використана на посівних секціях при посіві насіння цукрових буряків. Seeders press wheel of V-shaped profile consists of a bracket, on which the two-axis angle of the rim mounted. At the same time the profile of the rims is made saddle, and themselves rim placed vertically on either side of the line and are interconnected Prutkov frames, fixed on the disk hub having an exacerbation and mulching elements in the form of a straight four-sided pyramid.
Seeders press wheel